Abolishing Domein Verclaring in the Dominating Rights of Common Land in Indonesia - Rusyad, Zahir; Handoko, Widhi (International Conference of Moslem Society, 2018)
The implementation of PP. No. 24 year 1997 on Land Registration along with its derivates are still very close with the domein verklaring, but not all agrarian and spatial experts focus on the assessment of the domein verklaring practice. Land certification arrangement which is Land Registration System (PTSL) is still normative legatlistic. This matter can be read in the Requirement of Complete Land Registration System No. 1 year 2017 about the change of regulation of Agrarian and Affairs Spatial Ministry/Head of BPN RI No. 35 year 2016, on the Acceleration of the implementation of PTSL in Article 12 and so on. Land registration requires formal proof of all land rights objects. This means that indigenous land will not have place in the land registration system. Proof of common land rights can only be done anthropologically rather than normatively legalistic by showing formal letters, such as Letter D and C Desa. The formal requirement on the indigenous land proof creates a new style of domein verklaring. It triggers a lot of agrarian conflicts. Indigenous land conflicts will not be finished unless the verklaring domein ends with a progressive system which not merely based on formal proof. The policy of Ministry Agrarian and Affairs Spatial Planning/Head of BPN RI on One Map Polecy (one land registration map: the village land map & indigenous land) is on the right track but unfortunately technically the policy is not in line with the latest technological developments. The policy should lead to E-Certificate Land and On Line Service of land registration service through the application of Progressive Publicity Stelsel.